2017
DOI: 10.1083/jcb.201606077
|View full text |Cite
|
Sign up to set email alerts
|

Plk4 and Aurora A cooperate in the initiation of acentriolar spindle assembly in mammalian oocytes

Abstract: Establishing the spindle in mammalian oocytes after their prolonged arrest occurs in the absence of centrioles and is crucial for meiotic fidelity. Bury et al. show that this requires concerted activity of microtubule organizing center–associated Aurora A and Plk4, which are usually found at centrioles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 64 publications
8
75
0
Order By: Relevance
“…The structure of NuMA in acentrosomal cells was similarly formed in various cell lines derived from different human tissues, including nontransformed and hTERT‐immortalized human retinal pigment epithelium cells (RPE1; Appendix Fig S2C and D). It has been reported that PLK4 contributes to microtubule nucleation in oocytes (Bury et al , ). Thus, we examined whether the observed structure of NuMA could be attributed to the inhibition of PLK4 or to the low microtubule density induced by the removal of centrosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of NuMA in acentrosomal cells was similarly formed in various cell lines derived from different human tissues, including nontransformed and hTERT‐immortalized human retinal pigment epithelium cells (RPE1; Appendix Fig S2C and D). It has been reported that PLK4 contributes to microtubule nucleation in oocytes (Bury et al , ). Thus, we examined whether the observed structure of NuMA could be attributed to the inhibition of PLK4 or to the low microtubule density induced by the removal of centrosomes.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that kinases responsible for Pum1 phosphorylation are present and at least partially active in immature oocytes. Polo-like kinase (Plk) 1 and 4 were shown to be present in immature mouse oocytes (Bury et al, 2017; Pahlavan et al, 2000). Interestingly, inhibition of Plk4, but not that of Plk1, prevented the dissolution of Pum1 aggregates (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Centrosome‐driven and centriole‐independent pathways still require a common set of centrosomal and microtubule assembly promoting factors. The centrosome scaffold proteins Cep152 and Cep192 together with Plk4 are required to organize microtubules despite the absence of centrioles not only in mouse embryos but also during murine meiosis . γ‐TuRC, the key microtubule templating activity, remains essential for spindle formation in the absence or presence of centrosomes (Reviewed in: Ref.…”
Section: Spindle Formation In the Absence Of Centriolesmentioning
confidence: 99%